An efficient protocol for power consumption in wireless enterprise ad hoc virtual community network with Triso framework. (2018) - Manivannan, R.; Chinnadurai, M.
Today's global technology has various security treats which made the identity protection essential among user's for establishing communication over internet. Generally these identity protecting network were well known as anonymous communication networks. Mix networks are multistage systems which provide efficient mechanisms for anonymous communication over internet. According to which these networks have various traffic analysis attacks which need to compromise the identities of users. The major objective of this paper is to present a diversity mix techniques against traffic analysis attacks, disclosure attack and spam attack. In this work, we propose traffic re-allocation which involves in varying the size as well as number of messages in the network. By means of enabling this bursting and blending of messages among the network nodes the attacker get confused with the varied message count and sizes. The performance of our proposed work is examined against the three attacks in order to check its security and anonymity. The obtained result proves the effectiveness of our proposed techniques.